Virtual Health Library in Nursing for Colombia: a New Scientific Communication Portal - Cañon Montañez, Wilson (Investigación y Educación en Enfermería, 2017)
Abstract Scientific communication is understood as a set of socially shared dynamic processes and efforts, through which scientific knowledge is created, shared, and used. These processes also offer means and conditions for social interaction among the members of scientific communities, contributing to the production, dissemination, and use of knowledge and, consequently, to the advancement of science. (1) With technological progress, new tools have emerged from communication and information technologies (CIT) to disseminate scientific knowledge. The Virtual Health Library in Nursing (VHL in Nursing) is part of these new scenarios as thematic cooperation network and is an initiative from the region of IberoAmerica, which seeks to promote access to scientific information on nursing and establish alliances to maximize the shared use of CIT and collections of sources of information in Nursing.(2)